Development Model of Perinatal Death Surveilance and Response (PDSR) in Semarang City, Indonesia - Sutopo Patria Jati; Rani Tiyas Budiyanti; Nikie Astorina Yunita Dewanti; Ayun Sriatmi; Martini Martini (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2019)
The infant mortality rate is the important things to measure health status and achievement of Sustained Development Goals (SDGs). It can be used to audit the cause of perinatal death and used to planning program to prevent the death. In addition, data on perinatal deaths must be recorded in terms of population administration. The problem is underreported perinatal death so that data not valid. This is because many government stakeholder such as Health Office, Administrative Village, Family Empowerment and Welfare (PKK), and the Information and Communication Department has reported and recorded perinatal death themself but not integrated. This study aims to develop a concept of integrated perinatal death report and record. This research is qualitative research with following steps advocation, initial assessment, and development models through interview, observation, and Focus Group Discussion methods. The result of this study is existing condition and concept model that can integrate of perinatal death record and reported. The concept model in Semarang City, Indonesia can be done in two ways. First, data comes from the Health Office (SIM-KIA). Second, data comes from Administrative Village and Family Empowerment and Welfare (PKK). All of the data forwarded to the Integrated Data Integration System (SIDADU) in Information and Communication Service in Semarang City. To support the validity of data, the Health Office should identify all public and private health facilities related to perinatal care. The local government should release Circular Letter concerning the notification of services regarding the recording and reporting of perinatal deaths in Administrative Village.